Beiträge zur Klimatologie Westindiens - Blume, Helmut (ERDKUNDE, 1962)
The climate of the West Indies is decisively influenced by the great seasonal and regional changes of precipitation. The types of precipitation together with seasonal distribution and annual totales have been examined in order to gain a standardization and classification of climates. Types of precipitation. An interruption of the trade-wind currents and of precipitation is caused by the following weather conditions: in summer: 1) easterly waves, 2) the intertropical front moving forward to the north, and, 3) hurricanes, in winter: 1) weak convergences, 2) cold air-bridges from the north. The following areas can be distinguished according to the seasonal distribution of precipitation: 1) those with a rainy season in summer (one or two maxima of precipitation), 2) those with a rainy season in winter. The annual total of precipitation vary greatly from one place to another. Apart from a few exceptions such as the aridity of the Leeword Islands, this is a function of relief. The climatic classification of the West Indies is based on the seasonal pattern of humidity. Reichel’s Index proved to be most suitable for its determination in the area fringing the tropics, because, apart from giving the monthly mean precipitation and monthly mean temperatures, it also takes into account the number of days with precipitation per month, combining thereby the effectiveness and periodicity of precipitation. The ombro-thermal climatic classification of the West Indies is discussed with the help of isohygromenic maps using the islands of Hispaniola, Martinique, Barbados and Cuba as examples. The regional differences in the character of the climate depend largely on the relief. The mountain islands are, moreover, marked by thermal grades of altitude.